Retrospective study on the efficacy of one-stop synchronous versus asynchronous ablation for atrial fibrillation - KONG Xiangmeng, ZHANG Qingyong (Zhongguo linchuang yanjiu)
Objective To compare the efficacy of synchronous versus asynchronous catheter ablation (CA) combined with left atrial appendage occlusion (LAAO) in patients with atrial fibrillation. Methods A single.center retrospective analysis that included patients diagnosed with atrial fibrillation and treated with CA and left atrial appendage occlusion (LAAO) at Shanghai Ninth People's Hospital, Shanghai Jiao Tong University School of Medicine between October 2018and March 2023 was conducted. Participants were divided into two groups based on the timing of surgery: synchronous surgery group and asynchronous surgery group. The primary endpoints of the study were postoperative maintenance of sinus rhythm and incidence of complications, comparing differences in these endpoints between the two surgical approaches. Results Through propensity score matching analysis, a total of 229 patients were included, with 186 undergoing synchronous surgery and 43 undergoing asynchronous surgery. At 1 year postoperatively, compared to asynchronous surgery group, synchronous surgery group showed similar rates of atrial fibrillation recurrence (84.9% vs 94.1%, Log-rankP=0.175) and complication occurrence (2.7% vs 4.7%, χ 2=0.033,P=0.855). Conclusion Synchronous surgery is comparable to asynchronous surgery in reducing the recurrence rate of patients with atrial fibrillation. When selecting treatment strategies for atrial fibrillation, clinicians can consider synchronous or asynchronous surgery more flexibly based on individual patient circumstances.